Lingue di eredità a Napoli: Percorsi di inclusione sociale tra scuola e SPRAR - Di Salvo, Margherita (Incontri. Rivista europea di studi italiani, 2022)
Heritage languages in Naples This paper focuses on heritage languages in Naples (Italy). It discusses two different case studies (one Italian higher school and one Center for adult migrants) in order to individuate some possible external factors capable of having an impact on language maintenance and shift. It describes the functions of the heritage languages, Italian and Italian dialects have in schools, families and social networks for migrants of different generations and cultural origins.